PERENCANAAN PEMBELAJARAN TERINTEGRASI CULTURALLY RESPONSIVE TEACHING (CRT) DI SMP NEGERI 4 MALANG DAN SMP LABORATORIUM UM: PERSPEKTIF BERBASIS KARAKTERISTIK PESERTA DIDIK - Aisyah Adiningsih; Annisa’ Ayaturrahman; Anisa Maulida; Dita Mei Nurvitarini; Yuda Silma; Didin Widyartono; Aisyah Adiningsih; Annisa’ Ayaturrahman; Anisa Maulida; Dita Mei Nurvitarini; Yuda Silma (Universitas Negeri Malang, 2024)
The aim of this article is to provide a comprehensive review of integrated lesson planning with a Culturally Responsive Teaching (CRT) approach at SMP Negeri 4 Malang and SMP Laboratorium UM. This study employs a descriptive-comparative approach to compare lesson planning strategies between the two schools, focusing on how the planning considers the needs and characteristics of the students. Data were collected through classroom observations, tests, interviews with teachers, and reviews of lesson planning documents. In-depth analysis of the data reveals differences and similarities in the implementation of CRT at each school, as well as its implications for enhancing the success of learning relevant to the students' cultural contexts.